2011
DOI: 10.1002/jcp.22432
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H oxidase participates in the palmitate‐induced superoxide production and insulin secretion by rat pancreatic islets

Abstract: Nicotinamide adenine dinucleotide phosphate [NAD(P)H] oxidase complex has been shown to be involved in the process of glucose-stimulated insulin secretion (GSIS). In this study, we examined the effect of palmitic acid on superoxide production and insulin secretion by rat pancreatic islets and the mechanism involved. Rat pancreatic islets were incubated during 1 h with 1 mM palmitate, 1% fatty acid free-albumin, 5.6 or 10 mM glucose and in the presence of inhibitors of NAD(P)H oxidase (DPI--diphenyleneiodonium)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
1
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 72 publications
2
44
1
6
Order By: Relevance
“…The Nox holoenzyme consists of membrane and cytosolic components. The membrane-associated catalytic core consists of gp91phox and p22phox, and the cytosolic regulatory core includes p47phox, p67phox, p40phox, and Rac1 [20]. Under stimulatory conditions, the cytosolic components translocate to the membrane fraction for association with the catalytic core for Nox2 holoenzyme assembly and catalytic activation.…”
Section: The Impairment Of β Cell Function Induced By Oxidative Stresmentioning
confidence: 99%
“…The Nox holoenzyme consists of membrane and cytosolic components. The membrane-associated catalytic core consists of gp91phox and p22phox, and the cytosolic regulatory core includes p47phox, p67phox, p40phox, and Rac1 [20]. Under stimulatory conditions, the cytosolic components translocate to the membrane fraction for association with the catalytic core for Nox2 holoenzyme assembly and catalytic activation.…”
Section: The Impairment Of β Cell Function Induced By Oxidative Stresmentioning
confidence: 99%
“…Unlike first category of small G-proteins, requisite for posttranslational modifications and mechanism[s] involved in the activation of Rab GTPases under the physiological insulin secretagogues remains elusive. However, Rap1 is activated transiently by glucose 50 and undergoes carboxymethylation. 18, 51 The third group of small G-proteins consists of Rab2, Rhes and Rem2 which are under-studied, [52][53][54][55] whereas, RalA appears to draw direct regulatory effects in exocytosis.…”
Section: Small G-proteinsmentioning
confidence: 99%
“…Immunological localization and functional regulation of Nox have been described in clonal β-cells, rat and human islets. 50,75,90,92 Studies by Shen and associates in cardiac myocytes have also suggested regulatory roles for Rac1 in the activation of Nox and associated generation of ROS in animal models of diabetes. 93 In addition, significant increase in Nox-mediated oxidative stress and subsequent metabolic dysfunction has been clearly reviewed in a recent article by Kowluru.…”
mentioning
confidence: 99%
See 2 more Smart Citations